Territorios Indígenas versus colonizadores campesinos en Bolivia. Estudio de caso de la comunidad Indígena Yuracaré del río Ivirgarzama (CIYRI) - Benavides, Jean Paul (2022)
In the last 20 years, Bolivia has shown progress in the recognition of indigenous rights to land and forests for the development of traditionally excluded populations and as potential tools for environmental conservation. In this study, we use a variety of data collected over 15 years to delay the effect of the conflict between indigenous people and colonizers. We show that the recognition of territorial rights is not enough for indigenous populations in situations of conflict with other populations. Conflicts result in the degradation of resources, institutional weakening, and a general aggravation of their situation of vulnerability. The institutionalism of the Bolivian State acts in a biased manner and imposes great challenges for the fulfillment of indigenous rights.